2015
DOI: 10.2174/1871527315666151111122457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Contralaterally Controlled Functional Electrical Stimulation and Neuromuscular Electrical Stimulation on Upper Extremity Functions in Patients with Stroke

Abstract: Compared with the conventional NMES, CCFES provides better recovery of upper extremity function in patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…The study was powered based on data from Knutson et al (9) to detect differences in upper extremity FMA mean scores of 46.2 (standard deviation (SD) 2.1) in the CCFES group vs 41.1 (SD 2.2) in the NMES group at a significance level of 0.05 (10). A minimum of 4 participants per group was required in order to detect differences between groups with a power of 90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was powered based on data from Knutson et al (9) to detect differences in upper extremity FMA mean scores of 46.2 (standard deviation (SD) 2.1) in the CCFES group vs 41.1 (SD 2.2) in the NMES group at a significance level of 0.05 (10). A minimum of 4 participants per group was required in order to detect differences between groups with a power of 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CCFES has been developed as an active training, involving repetitive stimulation of peripheral neural activity, with bilateral symmetrical movement on the non-paretic side, to produce symmetrical and near-simultaneous movement of the paretic side. The patients control the timing and degree of WD in a way that does not interfere with the fluidity of task practice, making it more conducive to complete task-oriented functional hand activities (9,10,17). The effectiveness of CCFES was investigated in a RCT study conducted by Knutson et al in 2016 (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Recently, other investigators compared a variation of CCFES to cNMES in patients ≤ 3 months post-stroke (n=60), and showed that CCFES produced significantly greater gains than cNMES. 25 Unlike these previous trials, the present study included only stroke survivors with chronic hemiplegia (> 6 months), a population for which it is even more challenging to show positive benefits of rehabilitative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital of Nanjing Medical University, Nanjing, China E-mail: zhengyu8710@163.com it was safe for patients' skin (6). Knutson et al applied a pulse amplitude of 40 mA for all patients and 60 mA for one participant (7)(8)(9).…”
Section: Department Of Rehabilitation Medicine the First Affiliatedmentioning
confidence: 99%